Social learning and innovation cycles - Umberto Garfagnini; Bruno Strulovici (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2012)
We study social learning and innovation in an overlapping generations model, emphasizing the trade-off between marginal innovation (combining existing technologies) and radical innovation (breaking new ground). We characterize both short-term and long-term dynamics of innovation, and the intergenerational accumulation of knowledge. Innovation cycles emerge endogenously, but the number of cycles is finite almost surely, and radical innovation terminates in finite time. We identify a negative relationship between past successes and the magnitude of radical innovation, combining insights from the multi-armed bandit literature with a spatial representation of innovation. Past successes reduce the incremental value of experimentation, and result in less ambitious innovation. In our framework, patents promote radical innovation through two channels: by increasing the expected benefit of radical innovation and by increasing the cost of marginal innovation. Our analysis suggests that sustaining radical innovation in the long-run requires external intervention.
Keywords: D83; O3; 330; Social Learning; Innovation; Technological Change; R&D; Experimentation